2011
DOI: 10.1097/mph.0b013e3181fd2aae
|View full text |Cite
|
Sign up to set email alerts
|

Human Heme Oxygenase-1 Deficiency Presenting With Hemolysis, Nephritis, and Asplenia

Abstract: Heme oxygenase-1 (HO-1) is a stress-induced enzyme that catalyses the oxidation of heme to biliverdin. The primary deficiency of this enzyme has been shown in HO-1 knockout mice, and is characterized by intrauterine death and chronic inflammation. The first case of human HO-1 deficiency was reported in 1999. Human HO-1 deficiency has been observed to involve the endothelial cells more severely, resulting in hemolysis and disseminated intravascular coagulation. We report another case of human HO-1 deficiency in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
98
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(105 citation statements)
references
References 0 publications
6
98
1
Order By: Relevance
“…Studies in knock-out mice have shown that HO-1 deficiency is characterized by intrauterine mortality and chronic inflammation; over 95 per cent of HO-1 2 / 2 knock-out mice die in utero [6,7]. In the only two human cases of HO-1 deficiency reported to date [8,9], numerous anomalies were observed, including hemolysis, inflammation, nephritis, asplenia and early death [10]. Thus, HO-1 appears to play a critical role in normal cellular function in both laboratory animals and humans, largely due to conversion of a toxic molecule, heme, to cytoprotective molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in knock-out mice have shown that HO-1 deficiency is characterized by intrauterine mortality and chronic inflammation; over 95 per cent of HO-1 2 / 2 knock-out mice die in utero [6,7]. In the only two human cases of HO-1 deficiency reported to date [8,9], numerous anomalies were observed, including hemolysis, inflammation, nephritis, asplenia and early death [10]. Thus, HO-1 appears to play a critical role in normal cellular function in both laboratory animals and humans, largely due to conversion of a toxic molecule, heme, to cytoprotective molecules.…”
Section: Introductionmentioning
confidence: 99%
“…This distinguishes the phenotype from two published pediatric cases caused by HO-1 null-mutations with loss of enzyme function, which are not associated with HLH. 5,6 We show that the disease is clinically modulated by limiting heme challenge through calculated iron depletion, thus highlighting the importance of HO-1 function in oxidative stress defense and in the regulation of the macrophage-dependent inflammatory response.…”
mentioning
confidence: 99%
“…5,6,12,13 Both null-mutations and G139V cause hemolytic anemia with almost completely abolished bilirubin synthesis. Interestingly, in HO-1 -/-mice splenic macrophages are eliminated by the toxic effect of intracellular heme, resulting in splenic fibrosis and intravascular hemolysis.…”
mentioning
confidence: 99%
“…Of these isoforms, HO-2 and HO-3 are constitutively expressed, while HO-1 is inducible as a stress response to insults as hypoxia, hyperoxia, endotoxins. Reports of the rare and lethal genetic HO-1 deficiency in humans described severe dysfunctions as intravascular hemolysis and endothelial and renal damage [156] or asplenia and inflammation [157]. HO-1 null mice are characterized by retarded growth, anemia, susceptibility to stress, either oxidative or LPS-induced [158,159].…”
Section: Heme Oxygenase-1mentioning
confidence: 99%